Plastic Surgery on YouTube - Mohammed A. Almarghoub, MBBS; Muath A. Alghareeb, MBBS; AlAnoud K. Alhammad, MBBS; Haya F. Alotaibi, MBBS; Abdullah E. Kattan, MBBS, FRCS(C) (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. YouTube is the most accessed video website in the world. It hosts a variety of medical content. Plastic surgery-related content on YouTube has not been investigated before. In this study, we analyzed the most prevalent plastic surgery-related content available on YouTube.